An ‘extraordinary change’ in the Climate: The Transformative Power of Impressionism in George Moore’s Art Criticism - Fabienne Gaspari (Cahiers Victoriens et Edouardiens)
Oscar Wilde’s essay ‘The Decay of Lying’ introduces the idea of the transformative power of Impressionist painting, ‘this extraordinary change that has taken place in the climate of London’. Another Anglo-Irish writer, George Moore, underlined in his art criticism written in the 1880s and 1890s the radical transformations brought about by this pictorial movement. This article examines how George Moore responded to the disruptive nature of works by Whistler, Monet and Manet. It shows that the mutations generated by technological advances created new ways of seeing reflected in this new art. In a very insightful way announcing more recent studies, Moore’s texts focus on the shock produced by Impressionism and analyze its effects on the observer’s body. These writings try to transform the impression of disorientation felt in front of the pictures into an essential component of aesthetic experience. This feeling is also central to Impressionist literature and this article aims to study to what extent Moore’s ideas on the epistemological uncertainties characteristic of what he called ‘modern painting’ influenced the field of literature at the end of the 19th century and beginning of the 20th.